2021
DOI: 10.1002/adom.202001520
|View full text |Cite
|
Sign up to set email alerts
|

High‐Q Plasmonic Resonances: Fundamentals and Applications

Abstract: Subwavelength confinement of light with plasmonics is promising for nanophotonics and optoelectronics. However, it is nontrivial to obtain narrow plasmonic resonances due to the intrinsically high optical losses and radiative damping in metallic structures. In this review, a thorough summary of the recent research progress on achieving high‐quality (high‐Q) factor plasmonic resonances is provided, emphasizing the fundamentals and six resonant mode types, including surface lattice resonances, multipolar resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 293 publications
2
98
0
Order By: Relevance
“…Indeed, lattices of honeycomb-arranged nanoparticles generally exhibit better performance as compared to rectangular and hexagonal ones. [20] In this regard, Li et al [118] fabricated a honeycomb array of Al nanodisks by soft lithography (Figure 7c-1) able to support two high-quality SLRs over the visible and NIR range simultaneously (Figure 7c-2). This is a peculiar feature exhibited by the honeycomb lattice and, ultimately, it takes place thanks to its non-Bravais nature as suggested by the lack of the effect in similar hexagonal lattices.…”
Section: Slr-based Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, lattices of honeycomb-arranged nanoparticles generally exhibit better performance as compared to rectangular and hexagonal ones. [20] In this regard, Li et al [118] fabricated a honeycomb array of Al nanodisks by soft lithography (Figure 7c-1) able to support two high-quality SLRs over the visible and NIR range simultaneously (Figure 7c-2). This is a peculiar feature exhibited by the honeycomb lattice and, ultimately, it takes place thanks to its non-Bravais nature as suggested by the lack of the effect in similar hexagonal lattices.…”
Section: Slr-based Biosensingmentioning
confidence: 99%
“…For instance, exotic nanostructures such as nanocages, nanoscaffolds, and bow-tie nanoantennas exhibit higher field enhancement than conventional nanoparticles with smooth surfaces thereby representing a considerable advantage in applications relying on signal amplification such as surface-enhanced Raman spectroscopy (SERS), [11,12] surface-enhanced infrared absorption (SEIRA), [13,14] and plasmon-enhanced fluorescence (PEF). [15,16] In addition, when nanostructures are ordered in periodic arrays, new modes can arise as a result of the near-or far-field coupling among the localized plasmons so as to activate hybrid effects such as coupled LSPR (c-LSPR) [17,18] and surface lattice resonance (SLR), [19][20][21] respectively. Besides, plasmonic properties offered by metamaterials were recently investigated and sparked considerable interest since they demonstrated to offer significantly better performance as compared to metal-based nanostructures in many fields of applications such as biosensing, [22] photonics, [23] photovoltaics, [24] and optoelectronics.…”
mentioning
confidence: 99%
“…Among them, a feasible strategy is to explore the high-order plasmonic surface lattice resonances (SLR). [40][41][42] In 2021, Fang et al [43] proposed a horizontal metal-insulator-metal grating to generate quadrupolar plasmonic SLR at wavelengths of 1242 nm under oblique incidences, and their numerical results based on rigorous coupled-wave analysis declared the Q factor can reach 1036. In the same year, Bin-Alam et al [44] exploited SLR effects to construct a plasmonic metasurface with a Q factor up to 2340 in the telecommunication C band.…”
Section: Introductionmentioning
confidence: 99%
“…However, its quality factor (Q-factor) is relatively low (Q < 10) [ 8 , 9 ] to achieve ultra-narrow-band resonance due to the excessively high ohmic loss of the metal, thus resulting in the impracticality of potential applications based on surface plasmon resonance. In recent years, a large number of studies have extensively conducted and deeply explored the optical nanodevices that excite ultra-high Q resonance lines to overcome this defect, mainly focusing on: the resonators of high refractive index dielectric materials related to bound or quasi-bound states in the continuum excite the Fano resonance of high Q-factor through strong coupling between modes [ 10 , 11 , 12 , 13 , 14 , 15 ], and the plasma lattice resonance and Fano resonance based on periodic structure [ 8 , 16 , 17 , 18 , 19 , 20 , 21 ]. Researchers found that the bound state (BIC) in the continuum can be confined completely, without any radiation, and reach a high Q-value (10 4 ) [ 10 , 11 , 12 , 13 ], and the all-dielectric material not only eliminates the ohmic loss, but also the radiation loss of the magnetic response is low, and devices that respond through multipole high-Q resonance in the near-infrared band have been rapidly developed [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%